Exploring the Industrial Metaverse: Empowering Meta-Operators with Industry 5.0 Principles and XR Technologies - Kareem, Ali Noori; Chyad, M.A.; Salman Al-Gburib, Zahraa Dawood; Ibrahim, Husam Hamid; Sharaf, Hussien Kadhim (JOIV : International Journal on Informatics Visualization, 2024)
The term "Metaverse" has recently gained significant attention. It refers to a concept aiming to immerse users in real-time 3D virtual worlds using XR devices like AR/MR glasses and VR headsets. When this idea is applied to industrial settings, it's termed the "Industrial Metaverse," where operators leverage cutting-edge technologies. These technologies align closely with those associated with Industry 4.0, evolving towards Industry 5.0 and prioritizing sustainable and human-centric industrial applications. The Industrial Metaverse stands to benefit from Industry 5.0 principles, emphasizing dynamic content and swift human-to-machine interactions. To facilitate these advancements, this article introduces the concept of the "Meta-Operator," essentially an industrial worker guided by Industry 5.0 principles, engaging with Industrial Metaverse applications and surroundings through advanced XR devices. It also delves into the key technologies supporting this concept: Industrial Metaverse components, the latest XR technologies, and Opportunistic Edge Computing (OEC) for interacting with surrounding IoT/IIoT devices. Furthermore, the paper explores strategies for developing the next generation of Industrial Metaverse applications based on Industry 5.0 principles, such as standardization efforts, integrating AR/MR devices with IoT/IIoT solutions, and advancing communication and software architectures. Emphasis is placed on fostering shared experiences and collaborative protocols. Lastly, the article presents a comprehensive list of potential Industry 5.0 applications for the Industrial Metaverse and an analysis of the main challenges and research directions. It offers a holistic perspective and practical guidance for developers and researchers venturing into Industrial Metaverse applications.